(untitled) (Research, Society and Development, 2022)
Objective: This study aimed to evaluate how food can impact the development and improvement of the child’s general condition, bringing more quality of life. Methodology: This is a systematic literature review, using articles between the period 2010 to 2022. Through data carried out in specialized centers: Scielo, Google academic, Lume – Digital Repository of UFRGS, Pubmed. Results and discussion: The sensory effects due to children’s food selectivity, nutritional status and how the introduction of specific habits can help in better consumption and development were evaluated. Conclusion: After analysis, it is observed that patients have nutritional deficiencies and a selective pattern in food, so follow-up with the nutritionist is essential for a safe intervention.